(untitled) (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2023)
Injustice or discrimination against women continues to be seen in the media, one of which is in the film media in telling their stories. This problem is related to the depiction of women in films who are shown as helpless, deserving of being underestimated, and harassed. Issues related to gender injustice and discrimination manifest in the placement of women’s roles which are limited to the domestic sphere as housewives, helpers, and commodities to satisfy men’s desires. This problem is a perspective that places women as inferior beings. In films, especially horror films, this problem is still portrayed in a vulgar and caricatured way. Unlike most other Indonesian horror films, Perempuan Tanah Jahanam, directed by Joko Anwar, wants to present women as the main characters who have a central role in the story in the movie. The film portrays women as strong, brave, and unyielding figures. However, Joko Anwar has not automatically eliminated patriarchal values ??in the film Perempuan Tanah Jahanam. This is because filmmaking cannot be separated from the culture that develops in the local community and is value-free. Several scenes in the film still depict the existence of inferiority that applies to women. The author’s goal in conducting this research is to find the forms of female inferiority in the film Perempuan Tanah Jahanam. The method used in this research is the critical discourse analysis method from Sara Mills. The results obtained from this study are that forms of female inferiority are still found, as depicted in the film Perempuan Tanah Jahanam. This is due to the social construction that distinguishes men and women.